2018
DOI: 10.1016/j.cherd.2017.12.048
|View full text |Cite
|
Sign up to set email alerts
|

Resolving the rapid water absorption of porous functionalised calcium carbonate powder compacts by terahertz pulsed imaging

Abstract: Cost effectiveness, ease of use and patient compliance make pharmaceutical tablets the most popular and widespread form to administer a drug to a patient. Tablets typically consist of an active pharmaceutical ingredient and a selection from various excipients. A novel highly porous excipient, functionalised calcium carbonate (FCC), was designed to facilitate rapid liquid uptake leading to disintegration times of FCC based tablets in the matter of seconds. Five sets of FCC tablets with a target porosity of 45-6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 40 publications
0
39
0
Order By: Relevance
“…These disk-shaped blocks are described by the factor I that represents their radius to thickness ratio. The model was also shown to describe the relationship very well between porosity and tortuosity for functionalised calcium carbonate (FCC) tablets (Markl et al, 2018b). Wu et al, 2006 determined the fastest route through the pore space of sodium chloride compacts by analysing crosssections of the tablets using SEM.…”
Section: Tortuositymentioning
confidence: 99%
See 2 more Smart Citations
“…These disk-shaped blocks are described by the factor I that represents their radius to thickness ratio. The model was also shown to describe the relationship very well between porosity and tortuosity for functionalised calcium carbonate (FCC) tablets (Markl et al, 2018b). Wu et al, 2006 determined the fastest route through the pore space of sodium chloride compacts by analysing crosssections of the tablets using SEM.…”
Section: Tortuositymentioning
confidence: 99%
“…This < = parameter revealed that material attributes, such as particle size or granule density, strongly impact the anisotropy of the pore structure. The degree of anisotropy particularly influences the tortuosity and constrictivity of the structure and eventually the disintegration performance of the tablet (Markl et al, 2018b).…”
Section: Anisotropy Of Pore Structurementioning
confidence: 99%
See 1 more Smart Citation
“…The change in the effective refractive index and porosity clearly indicates the influence of elastic relaxation on the pore structure. This will in turn impact the liquid uptake rate that is part of the disintegration process of pharmaceutical tablets (Markl et al, 2018b). This post-compaction variation of the pore structure will also directly affect the dissolution performance.…”
Section: Optical Heckel Analysismentioning
confidence: 99%
“…Markl et al used a combination of terahertz pulse imaging, µCT, MIP and pycnometry together with an experimental setting for water sorption of FCC compacts. They interpreted the results as anisotropic pores that are perpendicular to the compaction direction of a tablet [30,31]. However, so far, no convincing data has been available which reveals the internal structure of single FCC particles.…”
Section: Introductionmentioning
confidence: 99%